Comparative Analysis Between Pre-Trading Volume Activities with Post Event Tax Amnesty - Bayu Teguh Imani; Satia Nur Maharani; Sheila Febriani Putri (AIBPM Publisher, 2020)
This study aims to determine the difference of Trading Volume Activity that exceed before and after the determination of tax amnesty policy and to figure out the existence of abnormal return formed before and after the determination of the tax amnesty. This study uses the Events Study method with 100 days observation for the estimation period and 15 days for event period. The study used a group of perception banks that listed in BEI in 2016 period as population and 22 selected stocks to be sampled by using saturated sampling method. During the observation period, positive and negative abnormal returns with fluctuating movements were formed. Trading Volume Activity changes between before and after-tax amnesty policy. From these two results, it can be concluded that there was leakage of information before the event published that indicates the form of market efficiency of Indonesia is half strong (semistrong form). Further research is suggested to use the calculation method and time period different from this research in order to obtain more accurate results.